THE EFFECT THERAPEUTIC COMMUNICATION AND MUSIC THERAPY ON ANXIETY OF PREOPERATIVE PATIENTS IN JENDERAL AHMAD YANI METRO CITY IN 2021 - Tumiur Sormin; Anita Puri; Septia Vivinarti (Jurnal Ilmu Keperawatan Indonesia, 2023)
Data in the world shows that 61% of perioperative patients experience anxiety for fear of experiencing pain during the operatio, if not overcome it can even delay the implementation of operation. This study aims to determine the effect of therapeutic communication and nusic therapy on preoperative patient anxiety, This type of research is quantitative approach with a quasi-experimental design using a pretest-postest with control group design. This sampling technique used accidental sampling. The population of this study was 80 respondents with a sample of 32 respondents devided into two group, namely the experimental group of 16 respondents and the control group of 16 respondents. The research was carried out in may-June at RSUD jenderal Ahmad Yani metro City in 2021. The results of this study indicate anxiety in the experimental group with the average value before being given action is 24,56, (SD= 3,741), (Min =19), (Max = 32), while the average value the average after being given the action was 12,13, (SD=1,544), (Min=10), (Max=15)., an the anxiety result in the control group with the average value before being given the actin is 15,13, (SD=2,680), (Min=11), (Max=20). It was concluded that there was a significant effect of therapeutic communication and music therapy  on prepperative patient anxiety with a p-value of 0,001. Therefore, it is recommended to the Jenderal Ahmad Yani Metro City to make therapeutic communication techniques and music therapy as companion therapy or additional relaxation therapy in preoperative patient.Keywords           : Therapeutic Communication, Music Therapy, Anxiety